'Am I not an Author?' Social class and the contemporary French novel. (3rd July 2019) - Chadderton, Helena
ABSTRACT: While the term 'working-class' has fallen out of usage as the concept of class has lost its visibility and its power as a métarécit, this does not mean the issues that this term evokes have gone away. The hardship that comes of particular working lives, as well as the values and culture which are distinct from dominant bourgeois values, still exist. Indeed, in a France and a Europe in which inequality is growing, and in which 'précarité' has become an everyday term, how is this reality represented in the contemporary French novel? Through a discussion of the relationships between class, society and literature, this article will explore the tensions between the literary world and the working-class novel. It will then turn to the work of contemporary writers Olivier Adam and Edouard Louis, who not only engage with issues of social class in their creative work, but equally condemn the disconnect between literature and society on the French literary scene. This article will show that working-class experience has potentially been sidelined not only as a result of the reduction in visibility of the very idea of social class, but also as a result of the French literary scene's approach to literature.